Ivermectin eliminated in heifers treated stool´s quantification - Moreno-Morales, Jenny Carolina; Andrade-Becerra, Roy José; Pulido-Medellín, Martín Orlando (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This study objective was to quantify the amount of ivermectin eliminated in the cattle feces, detected by the high performance liquid chromatography technique (HPLC), at the experimental farm Tunguavita in the Paipa city' Salitre townlet (Boyaca). It was experimented in 10 heifers of different breeds and weights with (the injection of) commercial Ivermectin at 1% in a O.2 mg/kg dose of alive body weight, subcutaneously in a single application. It was noted that at the second day to have applied the antiparasite, was obtained the highest corresponding concentration at 87.6%, and the lowest at 20 days after treatment, with a 0.17% concentration. That is, the Ivermectin concentration was decreasing by approximately 0.0535 ppm per day. No significant differences were found between breeds and weights of animals. This study results show that the presence of lvermectin in cattle feces, has a negative environmental impact on the copografa entomofauna, responsible for the degradation of the stool, as the different concentrations of Ivermectin continue their insecticide function, when eliminated in the stool. Fufthermore, it was determined that some part of the dewormer is being assimilated by the different individual internal organs and therefore it is not removed in its entirety.